PENGETAHUAN IBU HAMIL TENTANG GIZI SELAMA KEHAMILAN DI DESA SIALANG JAYA KECAMATAN RAMBAH KABUPATEN ROKAN HULU TAHUN 2021 - Eka Yuli Handayani; Ermiza; Mia Widiastuti (Maternity and Neonatal : Jurnal Kebidanan, 2021)
Nutrition is a process of using food that is consumed normally. Nutrition in pregnancy is a healthy and balanced diet that must be consumed during pregnancy. Assessment of the nutritional status of pregnant women can be known by the presence of weight gain during pregnancy, measuring the upper arm circumference (LILA), and measuring Hb. Nutrition plays a major role in maternal and child health. Poor maternal nutritional status will affect growth and development during pregnancy. The benefits of balanced nutrition during pregnancy are meeting the nutritional needs of the mother and fetus, achieving nutritional status under normal circumstances. Maternal weight before pregnancy and weight gain during pregnancy is less (underweight) or more (overweight) than normal will make pregnancy a risk (low risk). This study aims to determine the knowledge of pregnant women about nutrition during pregnancy in Sialang Jaya Village in 2021, the research method used is a descriptive method with a cross sectional research design. The population in this study were pregnant women, with a sample of 30 respondents. Sampling using Total Sampling. In this study, the measuring instrument used was in the form of a questionnaire as many as 20, while the data analysis was carried out by univariate analysis which resulted in a frequency distribution. The results showed that based on the knowledge of 30 respondents who had good knowledge as many as 3 respondents (10.0%), 13 respondents with sufficient knowledge (43.3%), and those with less knowledge were 14 respondents (46.7%). The conclusion from the research conducted by researchers is that the average knowledge of pregnant women about nutrition during pregnancy in Sialang Jaya Village 2021 is less knowledgeable. To increase knowledge, pregnant women should get information directly from health workers, social media, the environment and others related to pregnant women.